2011
DOI: 10.1055/s-0031-1296384
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Bioavailability of Two Dexamethasone Tablet Formulations in Indonesian Healthy Volunteers

Abstract: These results indicate that the two formulations of dexamethasone are bioequivalent and thus may be prescribed interchangeably.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
1
1
0
Order By: Relevance
“…Additionally, we compared the AUC(0-t) and Cmax from our study with previously published PK data. Following a PubMed search, we found eight human studies reporting AUC(0-t) and Cmax for orally administered dexamethasone doses between 0.5 mg and 300 mg.[ 12 19 ] Although two of these studies [ 12 , 18 ] reported deviating results for various reasons, overall, it was concluded that the pharmacokinetics of oral dexamethasone show linearity and that the AUC and Cmax obtained for Fortecortin (and Dexa ODF) in the current study fit in with current literature.…”
Section: Discussionsupporting
confidence: 60%
“…Additionally, we compared the AUC(0-t) and Cmax from our study with previously published PK data. Following a PubMed search, we found eight human studies reporting AUC(0-t) and Cmax for orally administered dexamethasone doses between 0.5 mg and 300 mg.[ 12 19 ] Although two of these studies [ 12 , 18 ] reported deviating results for various reasons, overall, it was concluded that the pharmacokinetics of oral dexamethasone show linearity and that the AUC and Cmax obtained for Fortecortin (and Dexa ODF) in the current study fit in with current literature.…”
Section: Discussionsupporting
confidence: 60%
“…Dexamethasone serum concentrations were determined by a reversed phase HPLC method, with ultraviolet detection at 240 nm, according to the method described by Harahap et al . Using 1 ml of serum the limit of quantification was 2.5 μg l −1 . The within run precision expressed as the relative standard deviation varied between 2.6% and 1.5% at concentrations between 15 and 85 μg l −1 .…”
Section: Methodsmentioning
confidence: 99%